2020
DOI: 10.1177/0218492320966434
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of single-dose cardioplegia in high-risk coronary bypass

Abstract: Background Despite the increasing popularity of single-dose cardioplegia techniques in coronary artery bypass grafting, the time window for successful reperfusion remains unclear. This study aimed to compare different cardioplegic techniques based on early and 30-day clinical outcomes via thorough monitoring. Methods This prospective cohort study included high-risk patients undergoing coronary artery bypass grafting and receiving 3 different types of cardioplegia between January 2017 and June 2019. Group 1 ( n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Supplemental Table 4, http://links.lww.com/JCM/A545 lists the 42 studies ultimately included in this meta-analysis 15–28,30–34,36–40,43,46–48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplemental Table 4, http://links.lww.com/JCM/A545 lists the 42 studies ultimately included in this meta-analysis 15–28,30–34,36–40,43,46–48 …”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA search flow diagram and checklist are available in Supplemental Figure 1 Supplemental Table 4, http://links.lww.com/JCM/A545 lists the 42 studies ultimately included in this meta-analysis. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][30][31][32][33][34][36][37][38][39][40]43,[46][47][48]…”
Section: Study Selectionmentioning
confidence: 99%
“…19,20 However, we did not notice any difference in favor of blood cardioplegia in our cohort, which is a similar finding to other reports on using the del Nido protocol in high-risk cases. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that del Nido cardioplegia had higher expression of inflammatory response and higher biomarker values in high-risk coronary artery bypass grafting procedures. 26 Those patients, however, present with completely different clinical profile and results cannot be directly compared to valvular procedures. This matter surely requires further investigation.…”
Section: Discussionmentioning
confidence: 99%